2003
DOI: 10.1021/jp0308514
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Titanium−Silicon Binary Oxide Thin Film Photocatalysts by an Ionized Cluster Beam Deposition Method. Their Photocatalytic Activity and Photoinduced Super-Hydrophilicity

Abstract: Titanium−silicon binary oxide thin films of differing TiO2 content were prepared by using an ionized cluster beam (ICB) deposition method using multi-ion sources under a dry preparation process. From the results of UV−vis absorption measurements, binary oxide thin films with low TiO2 content showed much higher transmittance as compared with the pure TiO2 thin film, indicating that the Ti−oxide species of these Ti−Si binary oxide thin films exist in a highly dispersed state within the SiO2 matrices. Ti K-edge X… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 25 publications
2
30
0
Order By: Relevance
“…However, as the light deactivates after 10 min, the contact angle continues increasing up to 12 degrees with the time delay of 20 minutes to light removal. Due to this characteristic of slight contact angle decrease with light irradiation and contact angle recovery with irradiation removal, it can be concluded that the film possesses photocatalytic properties [17].…”
Section: Resultsmentioning
confidence: 96%
“…However, as the light deactivates after 10 min, the contact angle continues increasing up to 12 degrees with the time delay of 20 minutes to light removal. Due to this characteristic of slight contact angle decrease with light irradiation and contact angle recovery with irradiation removal, it can be concluded that the film possesses photocatalytic properties [17].…”
Section: Resultsmentioning
confidence: 96%
“…The preparation of thin film materials in a high vacuum chamber have some potential advantages, as follows: (1) Contamination of the thin films with impurities can be prevented; (2) A dry preparation method does not require the use of any organic solvents so that it is an "environmentally-friendly process"; (3) Thin films with high crystallinity and strong adhesion can be easily prepared onto substrates without calcination at high temperatures; (4) The easy control of the various physical and chemical properties. We have successfully applied an ICB deposition method to prepare transparent TiO 2 -based thin films (Yamashita et al 1998a;Takeuchi et al 2000Takeuchi et al , 2001bTakeuchi et al , 2003aYamashita and Anpo 2004;Dohshi et al 2001;Anpo et al 2002). A schematic diagram of the ICB deposition method with multi ion-sources is shown in Fig.…”
Section: Ion Engineering Techniques For the Preparation Of Well-definmentioning
confidence: 99%
“…2 (Fukushima et al 1985). In the ICB deposition method, titanium vapor obtained by heating titanium metal as a source (Takeuchi et al 2001b(Takeuchi et al , 2003aDohshi et al 2001;Anpo et al 2002). The TiO 2 /SiO 2 and TiO 2 /B 2 O 3 ratios, film thickness and deposition rate (ca.…”
Section: Ion Engineering Techniques For the Preparation Of Well-definmentioning
confidence: 99%
See 1 more Smart Citation
“…Cluster-beam deposition has been used to coat 10× 10 mm 2 glass substrates with Ti-Si binary oxide films for photocatalytic decomposition of NO under UV light radiation 56) . Zhou et al 57) used combined clusterbeam deposition and metal ion implantation to produce nanostructured vanadium-doped TiO2 films that showed photocatalytic decomposition of formic acid even under visible light radiation.…”
Section: Catalysismentioning
confidence: 99%